Hubungan Desain Interior Terhadap Kenyamanan Pemustaka Di Dinas Kearsipan Dan Perpustakaan Provinsi Sumatera Barat - Vedri Rahmadhana; Heldi Heldi (Universitas Palangka Raya, 2023)
The interior design plays a very important role in today's modern era of modernization. It is evident that the beauty of a space greatly influences people's work activities and performance within it. A library, as a storehouse of knowledge, should consider the aesthetics of the space to allow patrons to work, learn, and create more freely in the library to meet their information needs, which will ultimately impact the patrons' loyalty to the library. The Provincial Archives and Library Service of West Sumatra still appears to be lacking in terms of aesthetics, furniture arrangement, noise levels, and the utilization of space, which is a significant concern for the library to make it more appealing to patrons as a place to seek information.